(untitled) (Global Journal of Management and Business Research, 2019)
In a corporation, management is employed by owners for specified functions from which utility of owners and management is to be derived. While executing their roles and obligations, management may consider fulfilling their interests at the expense of owners’ interests and vice versa. This results into agency problems. This study tests the relevance of the agency theory and examines whether existing governance mechanisms and ownership structure address agency problems in Savings and Credit Cooperatives (SACCOs) in Uganda. To accomplish this, a mixed research (both quantitative and qualitative) design is used. Self-administered questionnaire and personal interviews about: utility of owners and management, and governance mechanisms and ownership structure are administered onto the respondents-key informantsselected through stratified sampling of SACCOs in Uganda. Respondents’ perceptions about utility levels of owners and management, and governance mechanisms and ownership structure within the studied SACCOs; are analyzed using a 5-point Likert scale.